Study the Effect of Silymarin and Vitamin C in Skin Aging Induced by UVB Rays on the Mice Skin Redox System - HR Ahmadi Ashtiani; H Rastegar; AA Salarian; F Rahmani; Sh Rezazadeh; H Sedghi Zadeh (Institue of Medicinal Plants, ACECR, 2019)
Background: Exposure of the skin against occupational hazards is growing every day. Many scientists are trying to identify aspects about the mechanisms of damages done to the skin by them. The skin is the second metabolism organ of the body where redox-dependent metabolic pathways overcome. By considering the UV index, Iranians are at high risk of UVB damage by generation of reactive oxygen species (ROS) that leads to skin aging. Objective: In this study, we discuss the effects of the UVB rays on redox system; evaluate and compare the protective role of Silymarin and Vitamin C against UVB-induced skin aging. Method: Male Balb/C mice were divided into 6 groups of 6 mices: Silymarin, Vitamin C, Control, UVB exposed, UVB exposed treated with Silymarin and UVB exposed treated with Vitamin C. The inhibitory effect of Silymarin and Vitamin C for skin aging were determined by wrinkle formation, epidermal thickness and dermal inflammation. The anti-photo aging effects of Silymarin and Vitamin C have been assessed by SOD, GSH, GSH_PX and TAC kits. Results: The flake in UVB irradiated groups was significantly different (P<0.05). The mean length of the wrinkle in UVB irradiated group very significantly increased (P<0.01) and the collagen reduction, increased in very high significant different in aged control group (P<0.001). The mean TAC in VitaminC group increased very significantly high. (P <0.0001) Conclusion: The results indicate that the Silymarin and Vitamin C have anti-photo aging effects suggested to use in anti-wrinkle, anti erythematosus, anti-inflammatory topical cosmetics products.